SEMIOTICS ANALYSIS ON MELANCHOLIC MANDARIN POP MUSIC VIDEO ENTITLED WANDERING POET BY JOLIN TSAI - PRATAMA, HERMANTORO (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords : Semiotics, Signs, Music video, Mandarin popMandarin Music Video as one of entertainment media capture the prominent theme of the society. Entertainment media seem very helpful for the society to gain their solace because they can contemplate their experience through the video. This study examines the signs found in Jolin Tsai’s music video entitled Wandering Poet and interprets the meaning of each sign. This study is conducted to answer two problems: (1) What are the semiotics signs found in Jolin Tsai’s Music Video entitled Wandering Poet? (2) What are the interpretations of semiotics signs that found in the Music Video entitled Wandering Poet?.Since the study is related with interpretation in music video, the writer uses qualitative method by using document analysis as a proper method. The writer opted Jolin Tsai’s music video entitled Wandering Poet because the application of black and white has plentiful meanings which related to the prominent theme of Chinese society, isolation and loneliness. The writer accumulates the scenes and then places them based on theme and context. The writer only concentrates on drama scene rather than others since the signs mostly appear on it. In this study, the writer classifies the signs by using Peirce’s typology of signs (1958) and provides the interpretation of each signs indenotative and connotative forms. In order to get more appropriate meaning, thetheory of color by He (2009) is used to enhance the meaning of symbol based onChinese culture.The writer found all types of sign based on Peirce’s typology of sign (1958). The most frequently appearing type is Icon which is 162. Icons mostly appear in a form of visual object since it resembles a thing it signifies. The second frequently appearing type is symbol which is 75. Symbols appear in the form of text and ideas which is built by certain society. Then, the least frequently appearing type is Index which is 57. Indexes appear in the form of gesture and expression. of the actors.Signs appear in Jolin Tsai’s music video entitled Wandering Poet shows that all types of signs merge together to deliver a story.The influence of Chinese culture is very prominent in this video because most of the signs have Chinese elements within it. For the future researchers, the writer suggests to choose another type of music video such as performing based music video and concept based  music video for broaden variation in semiotic on music video.